2002
DOI: 10.1136/thorax.57.5.438
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of bacterial and viral pneumonia in children

Abstract: Background: A study was undertaken to investigate the differential diagnostic role of chest radiographic findings, total white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and serum C reactive protein (CRP) in children with community acquired pneumonia of varying aetiology. Methods: The study population consisted of 254 consecutive children admitted to hospital with community acquired pneumonia diagnosed between 1993 and 1995. WBC, ESR, and CRP levels were determined on admission. Seventeen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
208
8
30

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(268 citation statements)
references
References 21 publications
17
208
8
30
Order By: Relevance
“…The CRP concentration was not highly modified during the first 5 days, but an increase in concentration was observed at day 6 p.i. In human medicine it is widely accepted that viral infections cause minor increases in CRP concentration compared to that of acute bacterial infections [41]. This could explain the low response of this protein in this viral infection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The CRP concentration was not highly modified during the first 5 days, but an increase in concentration was observed at day 6 p.i. In human medicine it is widely accepted that viral infections cause minor increases in CRP concentration compared to that of acute bacterial infections [41]. This could explain the low response of this protein in this viral infection.…”
Section: Discussionmentioning
confidence: 96%
“…bacteria, virus, and trauma). It has often been suggested that in humans, viral infections caused a weaker response compared to that of acute bacterial infections [41]. However, not much is known about APP response elicited by viruses in pigs [2,11,35,38].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7,8 Bacterial pneumonia was defined as: a) suggestive chest X-rays and one or more clinical, microbiological or laboratory findings; b) non-suggestive radiological pattern but both clinical, laboratory and microbiological findings suggestive of bacterial pneumonia. Viral non-varicella pneumonia was defined as: a) suggestive radiological finding and one or more clinical, microbiological or laboratory findings; b) non-suggestive radiological viral but both clinical, laboratory and microbiological findings suggestive of viral pneumonia.…”
Section: Methodsmentioning
confidence: 99%
“…El patrón viral presenta hiperinsuflación, infiltrados peribronquiales, atelectasias y adenopatías hiliares. Diversos estudios han intentado correlacionar estos patrones radiológicos y otros exámenes de laboratorios complementarios como la VHS, PCR y el recuento de leucocitos, con etiologías determinadas [10][11] , concluyendo que la etiología bacteriana es más frecuente en pacientes con infiltrados alveolares específicamente lobares en la Rx de tórax, que los infiltrados intersticiales se ven en neumonías virales y bacterianas y que los exáme- nes complementarios no aportan mucho al diagnóstico etiológico, a excepción de la PCR.…”
Section: Radiología Y Exámenes Complementariosunclassified